Trading many goods with many countries: Exporters and importers from German manufacturing industries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
In Germany, for the reporting year 2009 transaction-level data on exports and imports of goods have been aggregated at the level of the exporting or importing firm for the first time. In these data the number of goods exported and imported and the number of countries exported to and imported from is reported, together with the values of these cross-border transactions. This paper uses these newly available data for firms from manufacturing industries to uncover new facts and to test theoretical hypotheses of the relationship between a core dimension of firm performance, namely productivity, and the number of goods traded and countries traded with.
Keywords: F14; 330; Exports; Imports; manufacturing firms; Germany; Mehrproduktproduktion; Außenhandelsstruktur; Exportindustrie; Importhandel; Verarbeitendes Gewerbe; Produktivität; Schätzung; Deutschland